Identifying the reasons of couples visiting the genetic centers in Tehran (1994) - Tahere Amir Hosseini (Iran University of Medical Sciences, 1996)
This is a descriptive survey with goal of identifying the reasons of couples visiting the genetic centers in Tehrann (1994).   The sample consisted of 150 couples randomly selected, in one of the mentioned Tehran genetic clinics.   The tool was two part questionnaire. The first part provided information of personal characteristics of the subjects (18 questions) and the second including 20 questions about the reasons of couples seeking consulation in the clinics.   The finding are presented in 46 tables and descriptive statistics were used for analyzing data.   In relation to the first specific objective (identifying demographic characteristics of subjects ) it was found that the most common age of men (34.7%) were between 24-29 years old while for females (36.4%) were 20-24 years and 35.7% of couples were in their first year of marriage for male decisions for marriager ( 36.7%).   The information sources of most males (36%) were family while for females were books (33.3%). The usage of magazines, clinics and mass media for males was 25.3% and 21.3% for females.   In relation to the second specific objective "identifying the couples reasons " 96.7% for having healthy child in future, 76.7% for genetic counseling in a genetic clinic after the birth of a child with a congenital anomaly, and 39.3% of units for miscarriage.   The findings showed still born and still-alive, also refered for genetic Counseling.   Finally suggestions on the basis of gained data for usage of information some researches were made.